Analisis Pengaruh Minat Generasi Milenial Dalam Menggunakan Produk Tabungan Emas di Pegadaian Syariah - Rosiyani, Novia; Hasyim, Fuad (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2021)
Pegadaian Syariah has issued a new product at the end of 2015, namely a gold savings product. However, not all millennials have good literacy regarding gold savings products at Pegadaian Syariah. Therefore, this study aims to determine the effect of promotion, knowledge, service quality, and motivation on the millennial generation's interest in using gold savings products at Pegadaian Syariah. This research was conducted with a quantitative approach method. The population in this study is the millennial generation which focuses on aspects of students living in Surakarta. The sampling technique used was quota random sampling with a sample of students from IAIN Surakarta, UMS, UNS, and STIE Surakarta. Data collection in this study used a questionnaire with a Likert scale. The data that was collected and processed in this study were 133 respondents. The analysis tool uses multiple linear regression analysis with SPSS application. Based on the results of the analysis, it can be seen that promotion (sig. 0.002<α), knowledge (sig. 0.004<α) and motivation (sig. 0.000<α) affect the millennial generation's interest in using gold savings products. Meanwhile, the service quality variable (sig. 0.086>α) has no significant effect on the millennial generation's interest in using gold savings products. In addition, the difference between campuses and campus dummy proxies does not have a significant difference in the millennial generation's interest in using gold savings products (sig. 0.808>α).